The Effects of Aspalathus linearis (Rooibos Tea) on Nitric Oxide (NO) and Cytokine Activity - Hoosen, Mujeeb (International Journal of Human and Health Sciences (IJHHS), 2019)
African plants have been used for medicinal purposes for many centuries. Many of these African medicinal plants are assumed to be safe but have yet to be scientifically validated. Aspalathus linearis (rooibos) is a commercialised South African tea recognised for its phytopharmaceutical potential. Aspalathus linearis (rooibos) has been gaining popularity globally for its health benefits and accepted as a nutraceutical due to the growing evidence of its efficacy. The bioactive constituents found in Aspalathus linearis (rooibos) have been reported to exert both anti-inflammatory and antioxidant activity however a few in vitro studies has suggested otherwise. Aspalathus linearis (rooibos) has shown to modify the actions of the immune system by influencing the regulation of messenger molecules like cytokines and nitric oxide however most of these studies have been conducted in vitro with a very few studies reaching in vivo application. Divergent in vitro cell models has shown to produce varying results regarding cytokine and nitric oxide NO activity of Aspalathus linearis (rooibos). This review highlights recent studies on the (NO) and cytokine activities of Aspalathus linearis (rooibos) both in vitro and in vivo. Most studies report on its anti-inflammatory and antioxidant activity however a few in vitro studies suggests opposite effects which should be considered for prolonged use especially when prescribed in a supplementation form. Many studies have looked at aspects of safety and toxicity of Aspalathus linearis (rooibos) however no complete toxicological studies have been done as yet. International Journal of Human and Health Sciences Vol. 03 No. 03 July’19. Page: 150-157